P47 Old manikins – new life. (November 2018) - Dickinson, Mike; Hatch, Mark
Abstract : Background: Manikins considered state of the art 5 years ago are now considered old fashioned, having been superseded or upgraded to 'improved' variants. Older manikins are frequently just packed away and stored in a cupboard, as was the case at Blackpool. However we have subsequently re-vitalised an old unit into productive educational tools. Summary of work: One of our former obstetric training manikins has been modified and adapted into a laparoscopic training simulator. We modified the abdominal section of a manikin, utilising pre-existing products and are piloting its use to train not only surgical techniques, but perhaps more importantly by utilising the original clinical feedback capabilities of the unit, we are able to challenge the whole surgical team. This 'whole body' experience allows us to produce scenarios that not only evaluate and develop clinical prowess but also the Human Factorial elements involved in surgical patient and team management.This is an ongoing process that is currently under evaluation but initial feedback is very positive. A number of royal colleges and NHS papers state that '…. Teams that work together should train together…' (1) highlighting the need to develop team training opportunities, whilst simultaneously maintaining engagement of individual clinicians – our concept achieves this. Whilst Human Factor training is an integral part of all our SBE processes this system will allow us to deliver training to individuals, as well as teams either in the skills unit or ' in situ ' in the actual operating theatre, allowing teams from multiple surgical specialties the opportunity to train together (figure 1). Results: The 'full body' surgical training system combines individual laparoscopic training opportunities with team training concepts and is an expansion of the training portfolio at Blackpool Teaching Hospitals that has only just been implemented at time of writing – initial feedback is very positive. Conclusion: Older manikins should not be just assigned to the store room or scrapped, if they are superseded or require expensive upgrades/repairs. Simulation education practitioners – 'simologists' – should not be afraid of modifying and thinking 'outside the box' as to how these precious commodities can be further utilised or adapted.